AVALIAÇÃO DO DESEMPENHO DE EDIFICAÇÃO-TESTE COM SISTEMA DE RESFRIAMENTO EVAPORATIVO INDIRETO ACOPLADO A PAINÉIS RADIANTES - Krüger, Eduardo; Fernandes, Leandro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The study was carried in a test-building, which was cooled by a roof pond coupled to radiant cooling panels. The location is arid and monitoring took place during summer 2017. Different configurations were compared to a base-case without any passive strategies. Configurations encompassed: shading, use of a roof-pond with or without floating insulation, coupling with radiant cooling panels, use of sprinklers. Results allowed us to determine the best configuration of the roof-pond/radiant cooling system.